Rancang Bangun Aplikasi Penjualan Berbasis Android Dengan Flutter Dan Laravel Menggunakan Metode RAD (Rapid Application Development) Pada Bengkel Mobil XCTOS - Abdurrahman Zaki; Nardiono (CV. Multi Kreasi Media, 2024)
XCTOS car repair shop is a line of business engaged in the fabrication and sale of car spare parts. In selling car spare parts, XCTOS auto repair shops still use conventional systems such as onsite visits and telephone agreements. What raises several obstacles is the small scope of product sales.To optimize sales of XCTOS auto repair spare parts products, in writing this thesis an Android-based sales application is made to display product information that has been produced by XCTOS auto repair shops. So customers can shop online anytime and anywhere with ease. Store admin becomes easier in carrying out the process of storing sales data and ordering products. Using a database so that existing sales data is recorded, organized, and not scattered. Store admins can manage data on the manage transactions menu on the XCTOS Admin web. With this Android-based sales application, sales transactions become easier. This spare parts sales application was built using the RAD (Rapid Application Development) method as a system development method. The programming languages used are Dart and PHP, the frameworks used are Flutter, Code igniter, and Laravel. The MySQL database is used as database storage, and software testing is carried out using the Blackbox Testing method. With this Android-based sales application, sales transactions can be carried out more easily and consumers don't have to come directly to the XCTOS car repair shop. as well as making sales data that has been recorded can be managed by the store admin in a more organized manner.